2018
DOI: 10.1021/acsomega.8b00524
|View full text |Cite
|
Sign up to set email alerts
|

Ga Ion-Enhanced and Particle Shape-Dependent Generation of Reactive Oxygen Species in X-ray-Irradiated Composites

Abstract: The reported results test the effects of the collective behavior hypothesized to contribute to the production of more reactive oxygen species (ROS) in vitro and result in an enhanced radiosensitization. The role of particle shape in composites with gallium oxyhydroxide (GaOOH) particles and Matrigel is studied. Particles of two different shapes are embedded into the gel to understand only the materials effect on the generation of ROS rather than cell penetrating variations. The paper reports materials characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[184] Other authors have also suggested a more efficient electron emission from smaller NPs, since the excited electrons have a lower probability of dissipating their energy inside the NP before reaching the surface. [227] The effects of NP shape on ROS generation, also widely observed, [228] and they can be attributed to a different mix of crystalline orientations with varying chemical activity. The effect of this orientation on the emission of electrons and reactive species generation is well established, for example, in water splitting by atanase and rutile TiO 2 NPs whose crystalline surface ordering differ.…”
Section: Effects Of Nanoparticle Size and Shape On Ros Generationmentioning
confidence: 99%
“…[184] Other authors have also suggested a more efficient electron emission from smaller NPs, since the excited electrons have a lower probability of dissipating their energy inside the NP before reaching the surface. [227] The effects of NP shape on ROS generation, also widely observed, [228] and they can be attributed to a different mix of crystalline orientations with varying chemical activity. The effect of this orientation on the emission of electrons and reactive species generation is well established, for example, in water splitting by atanase and rutile TiO 2 NPs whose crystalline surface ordering differ.…”
Section: Effects Of Nanoparticle Size and Shape On Ros Generationmentioning
confidence: 99%
“…A stable dispersion of metal nanoparticles is important for many biological applications and is dependent on nanoparticle shape and surface chemistry. While stable nanoparticles are preferential in biological studies due to biocompatibility [139], some studies suggest that a slight aggregation of nanoparticles increases cell uptake [102,120,150], Adams et al found the shape of gallium oxyhydroxide nanoparticles was influential on stability and thus on the generation of ROS. Their anisotropic shaped nanoparticles were found to be unstable in aqueous solutions and released gallium ions, leading to an increase in ROS generation, unlike the "orzo" shaped nanoparticle of the same surface chemistry [102].…”
Section: Dependence On Shape Structure and Stabilitymentioning
confidence: 99%
“…[ 63 ] GaOOH is demonstrated to be related with the generation of reactive oxygen species (ROS) in radiosensitization. [ 76,77 ] LMNPs can enable different shapes and composition, including sphere shape, rice shape, and rod shape (Figure 2d,e). [ 50,78 ] Several positive‐charged surfactants, such as cetrimonium bromide or lysozyme, are demonstrated to enable the shape morphing process upon heating, and the indium nanoparticles can be dealloyed as the by‐product.…”
Section: Synthesis Of Lmnpsmentioning
confidence: 99%